An experimental investigation into dispersion of compressive stress in isolated bottle-shaped struts with openings. (December 2020) - Fazeli Kelareh, Mohammadreza; Aghayari, Reza; Tahamouli Roudsari, Mehrzad
Abstract: Strut and Tie Modeling (STM) can be used to simplify intricate states of stresses within reinforced concrete (RC) members with geometric or static discontinuity regions (D-regions). A bottle-shaped strut can thus form when an isolated reinforced concrete compressed member is loaded in a relatively small area of the member or in the presence of an opening. In this category of struts, the resulting compressive stresses spread in a lateral direction as they have to avoid the opening area and the strut axis. In this respect, curving compressive stress trajectories give rise to notable transverse strains in an orthogonal direction to the strut axis and subsequently longitudinal cracks will form if insufficient reinforcement is arranged; which can lead to concrete failure. Therefore, an experimental investigation was conducted in this study to examine the dispersion of compressive stresses in isolated RC struts with openings. The size of the openings were kept constant in all specimens. The major parameters were presence of opening and opening location. Consequently, In the second part of the study (Analytical investigation), on the basis of model presented by Sahoo et al. (2009) [19] and based on the geometrical characteristic of the ILC, an analytical model was proposed to predict the load-carrying capacity of a bottle-shaped strut with an opening. This new proposed model considered the effect of size and position of the opening. To conduct the experimental study, five Isolated RC struts with compressive strength of 40  MPa (5800 psi.) and then different positions of openings were tested. Axial load, axial shortening and lateral strains were measured to determine the effects of the test parameters. The obtained results were also compared with an analytical equation of isostatic line of compression (ILC) and the American Concrete Institute (ACI) 318-11 Provision. These results indicated that the presence of an opening creates a variation on the dispersion of compressive stresses and consequently produce a reduction in load-carrying capacity.